Assessing the influence of ideologies on vote choice in an ethnoterritorial context: the case of Taiwan. (2nd September 2018) - Dupré, Jean-François; Medeiros, Mike
ABSTRACT: The literature on vote choice in Taiwan has regularly identified ethnoterritorial ideology – preference for independence or unification with China – as the main ideological cleavage in Taiwanese party politics. This paper contributes to the literature by investigating the effects of two more ideological dimensions on vote choice: social and economic. Based on data from the Taiwan Election and Democratization Study (TEDS) for the 2016 presidential and legislative elections, our findings demonstrate that social and (to a lesser degree) economic ideologies do have significant influence on vote choice, though ethnoterritorial ideology remains the primary ideological determinant. Findings were similar for the presidential and legislative elections. On this basis, we make a case for increased attention to social and economic ideologies in future research on vote choice in Taiwan, and we encourage scholars to study Taiwan in comparative perspective with other societies that are divided along ethnoterritorial lines.